2015
DOI: 10.1007/s11239-014-1165-3
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated platelets and antiplatelet therapy response in diabetic patients

Abstract: Increased platelet turnover and high level of reticulated platelets are associated with low response to antiplatelet therapy in diabetes mellitus type 2. This study evaluated association between percentage of reticulated platelets (%RP) and the response to antiplatelet therapy in patients with type 2 diabetes mellitus (T2DM). This prospective, pilot, case-control, clinical trial included 79 subjects stratified in three groups: group I included 30 patients with T2DM, group II included 34 non-diabetic patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
0
16
1
1
Order By: Relevance
“…Indeed, opposite findings have been previously reported by Mijovic et al, showing a correlation of the percentage of immature platelets with metabolic profile indicators and poor response to antiplatelet therapy, although including only 30 patients with type 2 DM (T2DM), that were compared with a control population including healthy subjects, with no cardiovascular risk factor, thus differing from the high‐risk profile patients included in our study, that might per se have conditioned the levels of IPF in our population . In fact, the levels of RPs in our population were slightly higher, also in subjects without diabetes, than in the studies by Lee et al or in the Serbian study, although not exceeding the estimated reference range …”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Indeed, opposite findings have been previously reported by Mijovic et al, showing a correlation of the percentage of immature platelets with metabolic profile indicators and poor response to antiplatelet therapy, although including only 30 patients with type 2 DM (T2DM), that were compared with a control population including healthy subjects, with no cardiovascular risk factor, thus differing from the high‐risk profile patients included in our study, that might per se have conditioned the levels of IPF in our population . In fact, the levels of RPs in our population were slightly higher, also in subjects without diabetes, than in the studies by Lee et al or in the Serbian study, although not exceeding the estimated reference range …”
Section: Discussioncontrasting
confidence: 96%
“…Finally, the use of the automated measurement of IPF instead of a direct assessment of RPs, might have conditioned our results, as the instrumental sorting of platelets can lead to the identification of more immature fractions and exclude certain small but young and fully active platelets. However, a good correlation has been previously reported between RPs and IPF and moreover, flow cytometric technique, based on RNA staining by thiazole orange, represents a complex and much less reproducible method for analysing the RPs, especially when aiming at the identification of a marker for a large‐scale assessment of cardiovascular risk.…”
Section: Limitationsmentioning
confidence: 99%
“…endothelial cells). [74] In addition to the increase in platelet reactivity, patients with diabetes exhibit increased platelet turnover, [85] which increases the proportion of new platelets with uninhibited COX-1 that enter the circulation. Newly formed, immature platelets likely contribute to the overall 'angry' platelet phenotype associated with diabetes because they have a greater mean volume and are more reactive than mature platelets.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…reduced production of TXA 2 ≥ 95%). [10,88] For example, the increased platelet turnover in patients with diabetes [75,76,85] combined with the short half-life of aspirin means that newly synthesized, hyper-reactive immature platelets remain uninhibited during a considerable portion of the 24-h window of time between once-daily aspirin doses. [11] Indeed, markers of immature platelets (i.e.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…Different results, instead, could be obtained from the direct determination of the number of reticulated platelets, that are those young platelets which display a larger size, higher granules and RNA content and increased capability of protein synthesis, and which have been described as the platelets with the greatest aggregating potential [42,43]. In effect, in a recent study Perl et al identified a significant impact of reticulated platelets on the response to prasugrel in 46 post-AMI patients, however, such findings certainly need to be verified in larger cohorts of patients and with other antiplatelet drugs [44].…”
Section: Discussionmentioning
confidence: 99%